KEANEKARAGAMAN JENIS KUPU-KUPU (Rhopalocera) DI RESORT TALANG LAKAT, TAMAN NASIONAL BUKIT TIGAPULUH - Agung Anugrah; Nurul Qomar; Yossi Oktorini (JURNAL ILMU-ILMU KEHUTANAN, 2020)
Bukit Tigapuluh National Park had a lot of natural resource potential that could be used as an ecotourism object, one of them is a butterfly. This study aims to identify the diversity of butterflies (Rhopalocera) species at Talang Lakat Resort TNBT. The observation method used in this research was the transect line that made in three observation locations at the Camp Granite ecotourism object. The results of the butterfly inventory were found 40 species was identified from 110 individuals, which belonged to five families. The species diversity index (H ') in each location was classified as moderate with the highest value was at the Waterfall (3.14).